Pembagian Harta Warisan Berdasarkan Pertimbangan Ekonomi - Ahmad Sainul (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
Islamic inheritance law is one of the sources of legal inheritance which regulates the affairs of a person who has left his property because he has died and that property will fall to the person who has rights.Soepomo said that the inheritance law makes regulations that regulate the process of directly transmitting and obtaining property and intangible goods from a generation of people to their descendants. This process has started while the parents are still alive. The process does not become acute due to the death of a parent. Indeed, the death of a father or mother is an important event for that process, but in fact it does not radically affect the process of succession and transfer of property and immovable property.A person has been designated as an heir because between the heir and the heir have a relationship of marriage, kinship and liberate slaves. Basically, most of the people prefer to solve inheritance problems by conducting family deliberation even though there have been stipulated rules in the Qur'an and al-Hadith. Basically, this family deliberation system is also allowed in Islamic law. However, there are exceptions in it if a dispute occurs during deliberation which results in an inheritance dispute